New Modalities for the Administration of Inhaled Nitric Oxide in Intensive Care Units After Cardiac Surgery or for Neonatal Indications: A Prospective Observational Study. (April 2018) - Gaudard, Philippe; Barbanti, Claudio; Rozec, Bertrand; Mauriat, Philippe; M'rini, Mimoun; Cambonie, Gilles; Liet, Jean Michel; Girard, Claude; Leger, Pierre Louis; Assaf, Ziad; Damas, Pierre; Loron, Gauthier; et al.
Abstract : BACKGROUND: Nitric oxide (NO) has a well-known efficacy in pulmonary hypertension (PH), with wide use for 20 years in many countries. The objective of this study was to describe the current use of NO in real life and the gap with the guidelines. METHODS: This is a multicenter, prospective, observational study on inhaled NO administered through an integrated delivery and monitoring device and indicated for PH according to the market authorizations. The characteristics of NO therapy and ventilation modes were observed. Concomitant pulmonary vasodilator treatments, safety data, and outcome were also collected. Quantitative data are expressed as median (25th, 75th percentile). RESULTS: Over 1 year, 236 patients were included from 14 equipped and trained centers: 117 adults and 81 children with PH associated with cardiac surgery and 38 neonates with persistent PH of the newborn. Inhaled NO was initiated before intensive care unit (ICU) admission in 57%, 12.7%, and 38.9% with an initial dose of 10 (10, 15) ppm, 20 (18, 20) ppm, and 17 (11, 20) ppm, and a median duration of administration of 3.9 (1.9, 6.1) days, 3.8 (1.8, 6.8) days, and 3.1 (1.0, 5.7) days, respectively, for the adult population, pediatric cardiac group, and newborns. The treatment was performed using administration synchronized to the mechanical ventilation. The dose was gradually decreased before withdrawal in 86% of the cases according to the usual procedure of each center. Adverse events included rebound effect for 3.4% (95% confidence interval [CI], 0.9%–8.5%) of adults, 1.2% (95% CI, 0.0%–6.7%) of children, and 2.6% (95% CI, 0.1%–13.8%) of neonates and methemoglobinemia exceeded 2.5% for 5 of 62 monitored patients. Other pulmonary vasodilators were associated with NO in 23% of adults, 95% of children, and 23.7% of neonates. ICU stay was respectively 10 (6, 22) days, 7.5 (5.5, 15) days, and 9 (8, 15) days and ICU mortality was 22.2%, 6.2%, and 7.9% for adults, children, and neonates, respectively. CONCLUSIONS: This study confirms the safety of NO therapy in the 3 populations with a low rate of rebound effect. Gradual withdrawal of NO combined with pulmonary vasodilators are current practices in this population. The use of last-generation NO devices allowed good compliance with recommendations.